Bacterial Isolates in Blood Culture of Children with Septicemia. - Al-Rawazq, Huda S.; Mohammed, Ali K.; Al-Zubaidy, Riyadh H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Septicemia is a common condition in children with a resultant high morbidity and mortality. It’s defined as the presence of bacteria in the blood and is often associated with severe infections, the alternative names (Blood poisoning, Bacteremia with sepsis, systemic inflammatory response syndrome). Objective: To study the etiological agents and antibiotics susceptibility of septicemia in children admitted to Central Teaching Hospitals of Pediatric. Patients and Methods: A total of 80 patients having signs and symptoms of Septicemia who were admitted to Central Teaching Hospital of Pediatric in Baghdad city. Samples were obtained during the period from the 1st January till the 30 th of February 2011. Bacteriological specimen (blood) collection, isolation and Identification of causative microorganism by colonial morphology, Gram stains, Biochemical tests and other tests used for further identification (Catalase, Coagulase, Oxidase test) and determining susceptibility of bacteria to antibiotics and chemotherapeutic agents. Results: The blood culture results showed that 20 (25.0 %) patients gave positive blood culture, 60 (75.0 %) patients gave negative blood culture. The microorganisms isolated from blood cultures of 20 patient gave positive blood culture with septicemia was Staphylococcus aureus 5 (25.0 %) Escherichia coli 5 (25.0 %), Klebsiella pneumonia 4 (20.0 %), Enterobacter spp 3 (15.0 %), Serreatia 2 (10.0 %), Pseudomonas spp 1 (5.0 %), and the frequency of septicemia in 20 case according to gender represented male 11 (55.0 %), female 9 (45.0 %). Conclusions: Positive blood cultures were obtained in 20 (25.0 %) of children. The commonest Gram positive bacterial isolate was Staphylococcus aureus and Gram negative bacterial isolate was Escherichia coli especially in males sex, in neonate age group who were delivered by cesarean section and preterm < 37 weeks gestational age. The antibiotics [Cefotaxime, Amoxicillin+ Clavulanic acid] are the most effective against Staphylococcus aureus and [Gentamycin, Amikacin, Imipenem] against Gram negative bacteria.